Pantothenate kinase-associated neurodegeneration (Hallerworden–Spatze disease): clinical aspects, diagnosis, treatment (literature review and own data) - Yu. H. Antypkin; L. H. Kyrylova; O. O. Miroshnykov; O. O. Yuzva; L. Yu. Silaieva; O. V. Berehela; L. A. Myroniak (Zaporožskij Medicinskij Žurnal)
Aim. To analyze current data of scientific literature on the etiology, pathogenesis, approaches to the diagnosis and treatment of rare orphan disease – pantothenate kinase-associated neurodegeneration and to describe the clinical case of this disease.